Efficient ultrafiltration-based protocol to deplete extracellular vesicles from fetal bovine serum. Issue 1 (1st January 2018) - Kornilov, Roman; Puhka, Maija; Mannerström, Bettina; Hiidenmaa, Hanna; Peltoniemi, Hilkka; Siljander, Pia; Seppänen-Kaijansinkko, Riitta; Kaur, Sippy
ABSTRACT: Fetal bovine serum (FBS) is the most commonly used supplement in studies involving cell-culture experiments. However, FBS contains large numbers of bovine extracellular vesicles (EVs), which hamper the analyses of secreted EVs from the cell type of preference and, thus, also the downstream analyses. Therefore, a prior elimination of EVs from FBS is crucial. However, the current methods of EV depletion by ultracentrifugation are cumbersome and the commercial alternatives expensive. In this study, our aim was to develop a protocol to completely deplete EVs from FBS, which may have wide applicability in cell-culture applications. We investigated different EV-depleted FBS prepared by our novel ultrafiltration-based protocol, by conventionally used overnight ultracentrifugation, or commercially available depleted FBS, and compared them with regular FBS. All sera were characterized by nanoparticle tracking analysis, electron microscopy, Western blotting and RNA quantification. Next, adipose-tissue mesenchymal stem cells (AT-MSCs) and cancer cells were grown in the media supplemented with the three different EV-depleted FBS and compared with cells grown in regular FBS media to assess the effects on cell proliferation, stress, differentiation and EV production. The novel ultrafiltration-based protocol depleted EVs from FBS clearly more efficiently than ultracentrifugation and commercial methods. Cell proliferation, stress, differentiation and EV production of AT-MSCs and cancer cell lines were similarly maintained in all three EV-depleted FBS media up to 96 h. In summary, our ultrafiltration protocol efficiently depletes EVs, is easy to use and maintains cell growth and metabolism. Since the method is also cost-effective and easy to standardize, it could be used in a wide range of cell-culture applications helping to increase comparability of EV research results between laboratories.